Strain effect in Pd@PdAg twinned nanocrystals towards ethanol oxidation electrocatalysis. Issue 1 (9th November 2021) - Huang, Jingbo; Liu, Qixing; Yan, Yucong; Qian, Ningkang; Wu, Xingqiao; Ji, Liang; Li, Xiao; Li, Junjie; Yang, Deren; Zhang, Hui
Abstract : Pd@PdAg bi-pyramids with a surface strain of 0.3% exhibited remarkably enhanced catalytic performance for the EOR compared to 2.1% strained icosahedra. Abstract : The strain effect is a critical knob to tune the catalytic performance and has received unprecedented research interest recently. However, it is difficult to distinguish the strain effect from the synergistic effect, especially in alloyed catalysts. Here we have synthesized Pd@PdAg icosahedra and {111} truncated bi-pyramids with only different surface strains between them as electrocatalysts for the ethanol oxidation reaction (EOR). Due to the same exposed facets and compositions of the two electrocatalysts, their EOR performances are mainly determined by the surface strains of PdAg alloys. These two electrocatalysts provide a perfect model to investigate the role of the strain effect in tuning the EOR performance. It is indicated that Pd@PdAg {111} truncated bi-pyramids with a surface strain of 0.3% show better catalytic activity and durability than Pd@PdAg icosahedra with a surface strain of 2.1% including commercial Pd/C. Density functional theory (DFT) calculations reveal that the lowered d-band center of 0.3% strained PdAg alloys relative to 2.1% strained ones reduced the adsorption energy of the acetate-evolution key intermediate *CH3 CO, thereby promoting the enhancement in the catalytic performance of Pd@PdAg nanocrystals for the EOR. Electrochemical analysis further verifies this demonstration on the key role of the strain effect in PdAg alloys for tuning catalytic performance.